2022 Thai Hypertension Society guidelines on home blood pressure monitoring. Issue 9 (4th October 2022) - Kunanon, Sirisawat; Roubsanthisuk, Weranuj; Chattranukulchai, Pairoj; Sangwatanaroj, Somkiat; Ophascharoensuk, Vuddhidej; Sitthisook, Surapun; Sukonthasarn, Apichard
Abstract: In 2021, the Universal Health Coverage Payment Scheme of Thailand approved home blood pressure monitoring (HBPM) devices for reimbursement. National utilization of HBPM devices will begin in 2022. This article provides the recommendations for HBPM from the Thai Hypertension Society. In this report, the authors review the benefits of HBPM and recommend confirming the diagnosis of hypertension by HBPM. Devices for HBPM should be the automated and validated upper arm cuff devices. HBPM should be ideally done for seven consecutive days before each clinic visit and take at least two readings (1 min apart) in the morning and before going to bed. The average blood pressure (BP) of 125–134/75–84 mmHg is classified as high normal BP and hypertension is BP of 135/85 mmHg or more. Target BP levels depend on the age of the patients; that is, < 125/75 mmHg for patients aged 18–65 years old, and <135/85 mmHg for patients over 65 years of age.